CRGD targeted and charge conversion-controlled release micelles for doxorubicin delivery. Issue 29 (2nd April 2015) - Guan, Xingang; Hu, Xiuli; Li, Zhihong; Zhang, Hong; Xie, Zhigang
<x xml:space="preserve">Abstract</x> A biodegradable polymeric micelle with cRGD targeting and charge-conversional moiety could enhance the cellular uptake of pharmaceuticals and result in high cytotoxicity to tumor cells.